Higher visual function deficits are independent of visual acuity measures in children with cerebral visual impairment - Chandna, A.; Wong, M.; Veitzman, S.; Menjivar, E.; Kulkarni, A. (Frontiers in Human Neuroscience, 2024)
Cerebral Visual Impairment (CVI), the leading cause of bilateral visual impairment in children, is characterized by Visual Acuity (VA) loss and Higher Visual Function Deficits (HVFDs). However, the relationship between VA loss and HVFDs remains unknown. A previous study using the Higher Visual Function Question Inventory (HVFQI) demonstrated that normal VA did not preclude HVFDs. In this prospective, controlled study of children with CVI, we examine the relationship between HVFDs and degrees of VA loss to extend our understanding of this relationship. We introduce two new indices -the spectrum and the severity of HVFDs to provide a comprehensive view of how CVI affects the individual child and the entire cohort. We also performed analysis for reliability of HVFQI to elicit HVFDs and present a preliminary analysis of the relationship between HVFDs and Age.Study participants included 59 children with CVI (age: 9.87 ± 3.93 yrs [mean ± SD]; binocular VA: 0.35 ± 0.34 log MAR.) and 120 Neurotypical (NT) children with normal visual acuity (age: 8.7 ± 2.8 yrs; binocular VA: 0.14 ± 0.16 logMAR). Clinical history and notes independently confirmed the diagnosis of CVI. Parents were interviewed with the HVFQI and response was recorded with 5-level Likert scale. Mann-Whitney U-test (MWU) determined reliability of HVFQI; Fisher's Exact Test (FET) and d-variable Hilbert Schmidt Independence Criteria (dHSIC) assessed independence between HVFDs and VA.Average spectrum (range 0-1) and severity (range 1-5) indices for CVI (spectrum: 0.65±0.24, severity: 3.1±0.77) and NT (spectrum: 0.12±0.17, severity: 1.42±0.49) were markedly different. MWU: p-value < 0.00001 confirmed reliability of HVFQI to distinguish CVI from NT children for both indices.The FET reported a p-value 0.202 which indicates that the data does not exhibit any relation between the HVFDs severity and VA. Analysis using dHSIC supports these findings (p-value 0.784). Based on these results, we urge that all children with suspected CVI should have an assessment for HVFDs in addition to VA measures. The HVFQI shows potential increase our understanding of the neural basis of visual perception, cognition, and visually guided action, and working towards a conceptual model of CVI, translating to clinical practice improvements.